Antibiotic-associated disorders of prothrombin synthesis and their probiotic correction with B. Clausii in breastfeed infants - Ivanko, O. G.; Solianyk, O. V. (Zaporozhye Medical Journal, 2018)
The aim of the investigation was to study the prothrombin test and PIVKA-II serum levels changes in infants aged 1-6 month after the broad-spectrum antibiotic treatment and determine the possibility of coagulation disorders correction with the help of probiotic Bacillus clausii strains OC, NR, T, SIN spores capable to produce vitamin K2. Materials and methods. The study involved 57 convalescents after an acute respiratory infection exclusively breastfed infants aged 1 to 6 months one week after the 7-day parenteral treatment with ceftriaxone. Among them 13 children with laboratory signs of blood hypocoagulation (INR >1.3) had received probiotic Bacillus clausii spores in a daily dose of 2 × 109 CFU for 10 days. Another 13 children who had not received a probiotic made up a comparison group. Laboratory data was compared with the results of 27 healthy children of the control group. Prothrombin test parameters as a prothrombin (PT), prothrombin time (PTT), international normalized ratio (INR) and protein induced by vitamin K absence or antagonist II (PIVKA-II) were determined using the hematologic analyzer COAGUCHEC XS and ELISA kit. Results. It was found that after antibacterial treatment in infants PT was decreased and reached only 50 % of the norm. At the same time, PTT and INR were increased up to 2-folds together with a significant PIVKA-II elevation, which is typical for vitamin K deficiency. The use of probiotic treatment within 10 days has contributed to normalization of prothrombin in 11 out of 13 observed infants versus 3 out of 13 in the comparison group (χ2 = 7,58 corrected by Yates, P < 0.05). Conclusions. Cephalosporin administration for breastfed infants can lead them to latent vitamin K deficiency development, which is manifested by high levels of PIVKA-II and signs of hypocoagulation development revealed by prothrombin test. The Bacillus clausii probiotic spores prescription to infants after antibiotic therapy course for 10 days normalizes the plasma prothrombin concentration while in children of the comparison group it remains lower than normal.